Respuesta :

Riia

The given expression is

[tex] (x-7)^2 [/tex]

which is equal to

[tex] (x-7)^2 = (x-7)* (x-7) [/tex]

Here we use distributive property ,

[tex] =x(x-7)-7(x-7) = x^2 -7x -7x+49 = x^2 -14x +49 [/tex]

Correct option is the first option .

We have to find the product

[tex] (x-7)^2 [/tex]

we can write it as

[tex] (x-7)(x-7) [/tex]

Now we have to apply the distributive property

=[tex] x(x-7)-7(x-7) [/tex]

= [tex] x^2 -7x -7x +49 [/tex]

= [tex] x^2 -14x +49 [/tex]

First option is the correct one